Avaliação do uso de placas de coalescência e filtros orgânicos em caixas de gordura para tratamento preliminar de efluente de laticínios - Batista, Aryane Pereira (2016)
In view of the large amount of oils and grease present in effluents from the dairy industry and considering the problems that can be caused by these compounds in the environment and in the biological treatment of effluent treatment plants, this study aimed to propose an efficient and low-cost solution to remove O&G from wastewater from dairy companies by evaluating three different settings of grease traps. Coalescence plates were inserted in one of the traps used and, in another trap, coalescence plates and an organic filter consisting of agricultural waste with sorption properties were inserted. The efficiency of both traps was compared to that of a traditional model of grease trap. In order to evaluate the performance of such systems, the following variables were monitored: oils and grease (O&G), chemical oxygen demand (COD), total phosphorus (TP) and total Kjeldahl nitrogen (TKN). Both the experiment and the laboratory analysis were performed at the Environmental and Sanitary Engineering Laboratory at the Federal University of Lavras – UFLA, and the wastewater used in the trials came from the Verde Campo Dairy Company (Lavras/MG). In the first trial, the traps were batch-tested operating in three filling cycles and hydraulic retention time (HDT) of 30, 60, 90 and 120 minutes. In order to increase the reliabilit y of the tests, the second one was performed in four replicates with the same HDT to evaluate the treatment systems. Only the modified grease trap was monitored at the highest HDT in the third test; however, the agricultural waste inserted in the trap varied: sugar cane bagasse, corn cob and eucalyptus sawdust were evaluated. Through the analyses of the efficiencies achieved by the grease traps in the first and second trials, it was possible to verify higher average efficiencies for the modified trap when it comes to removing all the monitored variables, including O&G, whose total efficiency reached was of 60%. Nonetheless, the trap containing only the coalescence plates was not significantly more effective than the conventional grease trap at the level of 5%. In the third evaluation, it was possible to observe that the corn cob was the waste which provided the best results in the removal of O&G and total P. On the other hand, the sugar cane bagasse was better in the removal of COD, while the sawdust was more efficient in the removal of TKN. Despite the difference between the filtering materials, all were efficient in the treatment of wastewater from the dairy industry. Therefore, it was possible to conclude that the modified grease trap has potential use in the dairy industry, and that, besides being better than the treatment systems available in the market, waste materials, which are widely available in rural and urban areas, can be used to build such trap.